Assessment of potential climatic scenario in Pahang state - Mohamad Shaiful, Mohd Shariff (2016)
The climate impact studies in the hydrology are often relying on the climate change information at a fine spatial resolution. However, Global Climate Models (GCMs) which is regarded as the most advanced models yet for estimating the future climate change scenarios are operated on the coarse spatial resolution and not suitable for climate impact studies. Future greenhouse gas (GHG) emissions are tile result of exceptionally complex element systems, dictated by driving strengths, for example, demographic development, socio-economic development, and technological change. This is because different scenarios will project different results. Therefore, in this study, the Statistical Downscaling Model (SDSM) was applied to downscale rainfall from the GCMs. The data from two rainfall station located in the Kampung Bandar Ulu Kechau Kuala Lipis and Ladang Teh Boh Cameron Highland were used as input of the SDSM model. Both stations located at Pahang State of Peninsular Malaysia. The study included the calibration and validation with large-scale National Centers for Environmental Prediction (NCEP) reanalysis data, and the projection of future rainfall corresponding to the GCMs-variables (HadCM3 A2&B2) and Precise A1b. The main objective of this research investigation is to study the climate change that will occur and affect Pahang state. Towards achieving the aim, other associated objectives are to determine appropriate scenario for Pahang State and to determine the future changes of rainfall trend affected by various type of scenarios. The study results shows that during the calibration and the validation stage, the SDSM model can be well acceptable in regards to its performance in the downscaling of the daily and annual rainfall. For the future period (2010-2099), the SDSM model estimates that there were increases in the total average annual rainfall and generally, the area of rainfall station become wetter.